2018
DOI: 10.1111/dme.13825
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease prevalence and risk factor prevalence in Type 2 diabetes: a contemporary analysis

Abstract: Aims To describe the prevalence of major cardiovascular disease (CVD) and risk factor control in a contemporary population with Type 2 diabetes. Methods We used data from the national registry in Scotland, Scottish Care Information‐Diabetes, linked to hospital admissions. Using descriptive statistics and logistic regression we described associations of risk factors with CVD. CVD was defined based on diagnostic codes in primary or secondary care data for ischaemic heart disease, cerebrovascular disease peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 21 publications
9
43
1
Order By: Relevance
“…(27) In the current study, weighted prevalence of NAFLD among individuals with diabetes was approximately 54%. In addition, NAFLD has been reported to increase the risk of morbidity and mortality in persons with diabetes, (28)(29)(30) which is consistent with the increased risk of diabetes mortality and large proportion of diabetes deaths associated with NAFLD noted in the current study. Similarly, NAFLD has been reported to increase the risk of LD progression and mortality.…”
Section: Discussionsupporting
confidence: 90%
“…(27) In the current study, weighted prevalence of NAFLD among individuals with diabetes was approximately 54%. In addition, NAFLD has been reported to increase the risk of morbidity and mortality in persons with diabetes, (28)(29)(30) which is consistent with the increased risk of diabetes mortality and large proportion of diabetes deaths associated with NAFLD noted in the current study. Similarly, NAFLD has been reported to increase the risk of LD progression and mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings to those of the present study were shown in two studies describing the real‐world use of glucose‐lowering therapies in patients at high CV risk using Scottish and United States‐based databases. Using a national registry linked to hospital admissions, a Scotland‐based study reported a higher percentage of patients with type 2 diabetes and established CV disease (44% of the total type 2 diabetes population, based on the LEADER inclusion criteria), and yet only 2.4% of this cohort were treated with a GLP‐1RA . Similarly, data from the US Diabetes Collaborative Registry showed that 48% of people with type 2 diabetes from a primary or secondary care setting would meet the same eligibility criteria for LEADER, but only 6% of these were prescribed a GLP‐1RA .…”
Section: Discussionmentioning
confidence: 99%
“…Scotland-based study reported a higher percentage of patients with type 2 diabetes and established CV disease (44% of the total type 2 diabetes population, based on the LEADER inclusion criteria), and yet only 2.4% of this cohort were treated with a GLP-1RA. 40 Similarly, data from the US Diabetes Collaborative Registry showed that 48% of people with type 2 diabetes from a primary or secondary care setting would meet the same eligibility criteria for LEADER, but only 6% of these were prescribed a GLP-1RA. 41 While it could be argued that the slow uptake of GLP-1RAs may be attributable to the reluctance of physicians to initiate injectable treatments in their patients with type 2 diabetes, analogous studies with oral glucose-lowering treatments with proven CV benefits, such as the SGLT2 inhibitor empagliflozin, showed a similar pattern to that observed with GLP-1RAs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of national registry data from Scotland showed that 83.6% and 71.1% of T2D patients with and without CVD were on a statin, respectively (5). Similar figures have emerged from analyses of Norwegian (6) and US populations (7).…”
Section: Introductionmentioning
confidence: 99%